2017
DOI: 10.17951/a.2017.71.2.33
|View full text |Cite
|
Sign up to set email alerts
|

The generalized Day norm. Part I. Properties

Abstract: In this paper we introduce a modification of the Day norm in \(c_0(\Gamma)\) and investigate properties  of this norm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…is an element of c 0 (here the k-th coordinate of x is repeated exactly k times and • p is the standard norm in lp). So we can apply the Day norm |||•||| β,p ( [3]) to the element u(x) and set…”
Section: The Generalized Day Norm and Renorming Of Banach Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…is an element of c 0 (here the k-th coordinate of x is repeated exactly k times and • p is the standard norm in lp). So we can apply the Day norm |||•||| β,p ( [3]) to the element u(x) and set…”
Section: The Generalized Day Norm and Renorming Of Banach Spacesmentioning
confidence: 99%
“…• L is such a Banach space. Next in [3] the authors introduced the generalized Day norm |||•||| β,p in c 0 and showed its properties. In this paper applying the generalized Day norm, we prove that for each 1 < p,p < ∞ in the Banach space (lp, • p ) there exists an equivalent norm • L,α,β,p,p such that (lp, • L,α,β,p,p ) contains diametrically complete set with empty interior.…”
Section: Introduction Recently E Maluta Presented a Reflexive Lurmentioning
confidence: 99%
See 1 more Smart Citation